2010
DOI: 10.1002/mds.23313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of the first Asian family with Parkinsonism related to SNCA triplication

Abstract: Triplication of SNCA is a rare cause of familial Parkinson's disease compared with duplication. Its clinical course is believed to be more robust than duplication, though it is uncertain. Marked as the first among the Asian population, we identified a Japanese family (paternal grandfather, father, and son) with SNCA triplication based on genetic and clinical analyses. The proband had a completely triplicated region including SNCA. This allele did not share any common haplotypes with those of previously reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Mutations in the α-syn gene have been identified to cause familial PD; in particular, triplication of the SNCA locus [85] was correlated with an early-onset and a rapid progressive DAergic phenotype [83], suggesting a toxic gain-of-function related to high protein levels. Consistently, α-syn-deficient mice display reduced susceptibility to environmental neurotoxins [21].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the α-syn gene have been identified to cause familial PD; in particular, triplication of the SNCA locus [85] was correlated with an early-onset and a rapid progressive DAergic phenotype [83], suggesting a toxic gain-of-function related to high protein levels. Consistently, α-syn-deficient mice display reduced susceptibility to environmental neurotoxins [21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this effect would be lost with mutation of the miR-7 target sequence and in the absence of the 3′-UTR, which confirmed that repression of α-synuclein expression by miR-7 requires the 3′-UTR of the α-synuclein mRNA. It has been confirmed that miR-7 actively represses α-synuclein protein expression; on the contrary, endogenous levels of α-synuclein protein are significantly increased by using specific anti-miRNA inhibitors against miR-7 31. Further, the expression of miR-7 is decreased in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) intoxicated mouse model of PD, which may contribute to the increased α-synuclein expression in this model.…”
Section: Mirnas and Sncamentioning
confidence: 97%
“…Later, several families with different ethnic background have been described, including members carrying four copies (triplication) or three copies (duplication) of SNCA (Table 1) (Wang et al 2013; Keyser et al 2010; Sekine et al 2010; Kojovic et al 2012; Darvish et al 2013; Olgiati et al 2015; Ferese et al 2015; Uchiyama et al 2008; Ahn et al 2008; Nishioka et al 2006, 2009; Chartier-Harlin et al 2004; Ibanez et al 2004, 2009; Sironi et al 2010; Pankratz et al 2011; Elia et al 2013; Konno et al 2016; Ross et al 2008; Kara et al 2014; Mutez et al 2011). In general, triplication generates very high expression of mRNA and protein molecules and influences the clinical manifestations of PD, causing severe forms of Parkinsonism similar to dementia with Lewy body.…”
Section: Copy Number Variations In Familiar Pd Genesmentioning
confidence: 99%